2020
DOI: 10.1186/s40795-020-00343-w
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent food insecurity in rural Sindh, Pakistan: a cross-sectional survey

Abstract: Background: Food insecurity (FI) is alarmingly high in developing countries including Pakistan. A quarter of Pakistan's population consists of adolescents yet there is no information on their experience of FI. FI at adolescent age have long term effect on mental and physical health hence we aimed to determine the prevalence of food insecurity (FI) among adolescents and compare it with household FI, and assess social determinants of adolescent FI. Methods: A cross-sectional survey on 799 households with unmarri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
4
9
1
Order By: Relevance
“…A highly significant and positive impact of large landholding on the food security of the household is observed. Because the family has more revenue, resources to enjoy prosperity as well as have more chances to be food secure, these results correlate with existing research findings (Harris-Fry et al, 2015;Seng, 2016;Sheikh et al, 2020). In Pakistan, mostly farming households own livestock and no doubt livestock has a positive association with the level of food security of the household (Munawar et al, 2013).…”
Section: Effect Of Socio-economic Characteristics On Household Food Securitysupporting
confidence: 81%
“…A highly significant and positive impact of large landholding on the food security of the household is observed. Because the family has more revenue, resources to enjoy prosperity as well as have more chances to be food secure, these results correlate with existing research findings (Harris-Fry et al, 2015;Seng, 2016;Sheikh et al, 2020). In Pakistan, mostly farming households own livestock and no doubt livestock has a positive association with the level of food security of the household (Munawar et al, 2013).…”
Section: Effect Of Socio-economic Characteristics On Household Food Securitysupporting
confidence: 81%
“…For example, the prevalence of FI in Kerman 15 was 34.3%, in Qazvin 16 43.9%, in Tehran 17 52.8% and Zahedan 18 58.8%. Literature reports that in developing countries like Ethiopia, Lebanon and Venezuela nearly 50% of the adolescents are found food insecure 10,19–21 . In another study in slums in northern India showed that the prevalence of FI was 51% 22 .…”
Section: Introductionmentioning
confidence: 96%
“…It is also a major concern that 42% and 27.3% of Pakistani women of reproductive age suffer from iron deficiency anemia and vitamin A deficiency, respectively. 5,10 With an increased cost of healthcare, high inflation rate, treating complications, and loss of productive life years, more importance should be given to preventive health, including the indispensable role of nutrition in reducing the risk of mortality and morbidity. 11 The Food and Agriculture Organization of the United Nations (FAO) defines food security as "When all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food, which meets their dietary needs and food preferences for an active and healthy life".…”
Section: Introductionmentioning
confidence: 99%